Determinants of outcome in Covid-19 hospitalized patients with lymphoma: A retrospective multicentric cohort study. (October 2020) - Lamure, Sylvain; Duléry, Rémy; Di Blasi, Roberta; Chauchet, Adrien; Laureana, Cécile; Deau-Fischer, Bénédicte; Drenou, Bernard; Soussain, Carole; Rossi, Cédric; Noël, Nicolas; Choquet, Sylvain; Bologna, Serge; et al.
Abstract: Background: Patients with lymphoma are immunocompromised because of the disease per se and its treatments. We aimed to describe the characteristics of patients with lymphoma hospitalized for Coronavirus Disease 2019 (Covid-19) and to analyze pre-Covid-19 determinants of mortality. Methods: This retrospective multicentric cohort study used the Programme de Médicalisation des Systèmes d'Information database to identify all adult patients with lymphoma, hospitalized for Covid-19 in March and April 2020, in 12 hospitals of three French regions with pandemic outbreaks. The characteristics of lymphoma and Covid-19 were collected from medical charts. Findings: Eighty-nine patients were included. The median age was 67 years (range, 19–92), 66% were male and 72% had a comorbidity. Most patients had B-cell non-Hodgkin lymphoma (86%) and had received a lymphoma treatment within one year (70%). With a median follow-up of 33 days from admission, 30-day overall survival was 71%, (95% confidence interval, 62–81%). In multivariable analysis, having an age ≥ 70 years (hazard ratio 2·87, 1·20–6·85, p  = 0·02) and relapsed/refractory lymphoma (hazard ratio 2·54, 1·14–5·66, p  = 0·02) were associated with mortality. Recent bendamustine treatment ( n  = 9) was also pejorative (hazard ratio 3·20, 1·33–7·72, p  = 0·01), but was strongly associated with relapsed/refractory lymphoma. Remarkably, 30-day overall survival for patients < 70 years of age without relapsed/refractory lymphoma was 88% (78% - 99%). Interpretation: Thirty-day mortality was associated with being older and relapsed/refractory lymphoma. Survival of patients younger than 70 years without relapsed/refractory lymphoma was comparable to that of the general population. Funding: There have been no specific funds to run this study.